Identificação do transtorno do desenvolvimento da coordenação em crianças quilombolas - (:unkn) unknown (ICSEZ - Instituto de Ciências Sociais, Educação e Zootecnia (Parintins), 2024)
The Developmental Coordination Disorder (DCD) is classified as one of the neurodevelopmental disorders with an unknown cause that significantly and persistently interferes with the performance of daily activities. It impacts academic/school productivity, pre-professional, professional, and leisure activities. This study aimed to identify children from quilombola communities in the Lower Amazon River region who show signs of DCD. The sample consisted of 125 children of both sexes, aged between seven and ten years. To identify DCD, the Motor Coordination Traffic Light Questionnaire (MC-TLQ) and the Movement Assessment Battery for Children - Second Edition (MABC-2) were used. It was observed that 8.8% of quilombola children exhibited some alteration in motor coordination development. This result is promising, suggesting that future studies should carry out further steps in identifying and diagnosing DCD in this population.
Keywords: Transtornos do neurodesenvolvimento; Déficits motor; Quilombos; CIENCIAS DA SAUDE